قياس أثر أهم العوامل الاقتصادية على انبعاثات الكربون: تحليل قطاعي زمني - Soliman, Hebatallah (مجلة العلوم الإدارية و الإقتصادية, 2018)
This paper is trying to measure the effect of trade openness, economic development, FDI, energy consumption and urbanization on Carbon emissions, using Panel data over the period 1982-2014 in 86 countries, division the panel based on the income level in to 4 income panels; high income, upper middle income, lower middle income and low income. Using Panel Cointegration Analysis. Results showed that: energy consumption, economic development, trade openness and urbanization are have positive effects on CO2 emissions. while the FDI is have a negative effect on CO2 emissions in the global panel. The results of Granger causality showed that: energy consumption, economic growth, and trade openness are the main causes of carbon emissions in the global panel and both high and middle-income countries, Which required increase the investment in clean energy. For middle-income countries, FDI is not a cause of carbon emissions, requiring set clear criteria to encourage clean investments.